Socio-economic contributions of tourism in the development of hospitality industry - Amaechi Anyadighibe, Joseph; Kechi Kankpang, Alphonsus; Kekung Bessong, Peter; Joel Efiong, Eme; Usang Inah, Egu (Edelweiss Applied Science and Technology, 2024)
This study examines socio-economic contributions of tourism in the development of hospitality industry in Cross River State, Nigeria. The economic impact analysis (EIA) was adopted as the underpinning theory for the study. It helps in analysing the contributions of an industry to the economy of a region. The researcher used cross sectional survey method, non-probability purposive method and quantitative method (multiple regression) to analyse 232 staff of hotels, restaurants, eateries and dining in Calabar metropolis, Cross River, Nigeria. Findings from the study show that the socio economic contributions of tourism (income generation, foreign exchange earnings and employment opportunities) increases revenue, improve the quality of services and facilities of hospitality industry and relieves government of the responsibility of been the sole employer of labour. The research results provide an insight on the importance of developing nations investing in tourism as the gate way to development of hospitality industry. Research results have identify socio economic contributions of tourism as the key to sustainability of hospitality industry in the area of revenue generation, improvement in services and facilities to state of art and reducing pressure on government in the area of employment.